The Role of Trust in the Intention to Continue Using Mobile Payment Applications in Indonesia: A Case Study of Gen Z in Batam City - Ikhlash, Muhammad; Purba, Theresia (Journal of Applied Accounting and Taxation, 2025)
This study aims to evaluate how trust influences the intention of Generation Z in Batam City to continue using mobile payment applications. Using a quantitative approach, data were collected from 348 respondents through a survey and analyzed using the SEM-PLS method. The analysis included tests for validity (AVE, loadings), reliability (Cronbach’s Alpha, Composite Reliability), model fit (SRMR), path analysis using bootstrapping, and moderation testing using MICOM and Multi-Group Analysis (MGA). The findings indicate that security and application reputation have a positive and significant effect on building user trust. In contrast, mobility and customization do not show a significant impact. Trust is proven to significantly reduce risk perception and enhance the intention to continue using the application. On the other hand, risk perception negatively affects the sustainability of application usage. The moderation analysis using MICOM and Multi-Group Analysis reveals that gender does not significantly moderate the relationship between antecedents and trust. These findings underscore the crucial role of security and reputation in cultivating user loyalty among Gen Z mobile payment users.